2013
DOI: 10.1088/0957-0233/24/4/045102
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional object location and inversion of the magnetic polarizability tensor at a single frequency using a walk-through metal detector

Abstract: A tomographic metal detection and characterisation system has been designed and built for recovering information about magnetic and/or conductive objects within the detector space. This information is gathered as a result of a "walk-through" scan of a candidate in the same manner as for a typical security metal detector archway. Following the passage of the candidate, the system uses measurements from an array of coils to calculate the polarisability tensor, which describes the low frequency electromagnetic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 7 publications
4
54
0
Order By: Relevance
“…Previously, it has been used to improve electrical imaging [1] (for biomedical or industrial purposes) as well as investigating electrosensing fish [2,3,4,5,6,7] and also metal detection for security screening [8,9,10] or landmine clearance [11,12,13]. It arises from the studies about the perturbation of electric or electromagnetic field in a free space (such as 2D or 3D) due to the conductivity contrast between the space itself and some small conducting objects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been used to improve electrical imaging [1] (for biomedical or industrial purposes) as well as investigating electrosensing fish [2,3,4,5,6,7] and also metal detection for security screening [8,9,10] or landmine clearance [11,12,13]. It arises from the studies about the perturbation of electric or electromagnetic field in a free space (such as 2D or 3D) due to the conductivity contrast between the space itself and some small conducting objects.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples regarding computation of the PT based on the explicit formula and according to the geometry as well as the material of a conducting object can be found in [17,20,21,22,23]. On the other hand, the PT is sometimes referred as the polarizibility tensor in engineering literatures and can be obtained from field measurements either in laboratory or fieldwork [8,9,10,12,13]. Since the measurements can be made as long as there is a conducting object perturbing the electric or electromagnetic field, any other information about the object is not needed to find the PT (see Makkonen et al [10]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we know the tensor of the object beforehand, we can use it to distinguish different metallic objects from one another purely from their magnetic response. This approach has significant application in areas such as walk-through metal detectors [3], [4] and in landmine detection and clearance [5].…”
Section: Introductionmentioning
confidence: 99%
“…The design of a system which is capable of identifying buried or visually obscured metallic items has the potential to significantly reduce the time required to clear a given area of threats. Our previous research has shown the possibility of inverting the magnetic polarisability tensor, ↔ M, and its use in classifying targets [7] [8].…”
Section: Introductionmentioning
confidence: 99%